Classification performance of semi-inverted hydrocyclones. (October 2019) - Rasyid, Muhammad Abdur; Jokovic, Vladimir; Morrison, Robert
Highlights: Semi-inverted hydrocyclone reduces the misclassification of fines. The cut size for a semi-inverted cyclone is higher than for conventional hydrocyclone. The change of cone angle has extened the operational range of a semi-inverted hydrocyclone. Abstract: Researchers have reported in the past that inclined hydrocyclone operation can provide a lower water split to underflow and much coarser cut sizes. However, semi-inverted hydrocyclones (inclined higher than the horizontal position) have not been investigated in detail. This paper presents the results of a comprehensive study that was carried out at the Julius Kruttschnitt Mineral Research Centre (JKMRC) using a semi-inverted (SIV) hydrocyclone. A 250 mm hydrocyclone was tested with a modified cone. The modified cone extended the operational range of the hydrocyclone. The SIV hydrocyclone was tested at different inclinations and operating feed pressure using three different slurry feeds. A significant reduction in the water split (WS) to coarse was achieved at semi-inverted positions. WS values of 3–5% at 135° inclination were achieved. The change in WS did not influence the sharpness of separation (α). Stable operation and sharpness of separation were achieved, despite the appearance of roping-like underflow discharge in semi-inverted operation.